(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تنتمي الإيستروجينات، موضوع البحث، إلى مجموعة المركبات المعطلة للإندوكرين، والتي أخذت تثير اهتماماً كبيراً ومتزايداً نتيجة لتزايد الأدلة على تأثيراتها السلبية في النظم المائية والإنسان. قيست تراكيز كل من 17 بيتا إيستراديول ((E2 و 17 ألفا إيتينيلإيستراديول(EE2) في كل من مياه الدخل، ودفوق الترسيب الأولي والثانوي، ومياه الخرج في محطة معالجة مياه الصرف الصحي بعدرا، وذلك عبر اعتماد شروط تحليلية جديدة بتقانة الكروماتوغرافيـا السائلة عاليـة الأداء. كان حـد التقديـر الكمـي لكـل من E2و EE2 6.4 و 7.6نانوغرام/ل على التوالي. أظهرت النتائج أن تراكيز E2 و EE2 المقيسة في مياه الدخل كانت في المجالين (51 – 75) و (17 – 54) نانوغرام/ل على التوالي، وقد انخفض تركيز كل منهما مع تقدم المعالجة، حيث بلغت نسبة انخفاض التركيز في دفوق الترسيب الثانوي46%) ) و ( 42.35%) من أجل E2 و EE2 على التوالي. ولم يتم الكشف عن المركبين في أي من العينات المأخوذة من الدفوق النهائية. تشير نتائج الدراسة إلى فعالية المعالجة الحيوية في إزالة الإيستروجينين المذكورين بشكل تام ضمن حدود الكشف، بالرغم من ذلك نؤكد أهمية تطبيق معالجة متقدمة لضمان أفضل النتائج، أو تعزيز فعالية الإزالة للمعالجة الحيوية كخيار اقتصادي فاعل عبر تعديل شروط التشغيل. Estrogens belong to the Endocrine disrupters of which there is growing concern in recent years, since more and more evidence has been gathered showing their adverse effects on both aquatic systems and humans. Concentrations of 17 beta estradiol (E2) and 17 alpha ethinyloestradiol (EE2) were determined in the influent, effluents of primary and secondary settling tanks, and final effluent of the sewage treatment plant in Adra by applying a new analytical procedures using HPLC. Limits of Quantification (LOQ) were 6.4 and 7.6 ng/l for E2 and EE2 respectively. The results showed that levels of E2 and EE2 measured in the influent were in the range of (51-75) and (17-54) ng/l respectively. The concentration decreased with the progress of treatment, as the reduction ratio of E2 and EE2 in the secondary effluent were 46% and 42.35% respectively. No concentrations were detected in the final effluent. The results indicate that conventional treatment is efficient in the removal of estrogens, stressing the Importance of applying advanced process to achieve the best results, or promoting the removal effectiveness for biological treatment as an efficient and cost effective option by modifying the operating parameters.